Leishmania donovani Inhibitor of Serine Peptidases 2 Mediated Inhibition of Lectin Pathway and Upregulation of C5aR Signaling Promote Parasite Survival inside Host - Verma, Sudha; Mandal, Abhishek; Ansari, Md. Yousuf; Kumar, Ajay; Abhishek, Kumar; Ghosh, Ayan Kumar; Kumar, Ashish; Kumar, Vinod; Das, Sushmita; Das, Pradeep (Frontiers in Immunology, 2018)
ABSTRACT Leishmania donovani, the causative agent of Indian Visceral leishmaniasis (VL) has to face several barrier of the immune system inside the mammalian host for its survival. The complement system is one of the first barriers and consists of a well-balanced network of proteases including S1A family serine proteases (SPs). Inhibitor of serine peptidases (ISPs) is considered as inhibitor of S1A family serine peptidases and is reported to be present in trypanosomes including Leishmania. In our previous study, we have deciphered the role of ISPs (LdISP1 and LdISP2) in the survival of Leishmania donovani inside the sandfly midgut. However, the role of theses ISPs in the survival of L. donovani inside mammalian host still remains elusive. In the present study, we have deciphered the inhibitory effect of LdISPs on the host complement S1A serine peptidases such as C1r/C1s and MASP1/MASP2. Our study suggested that although both rLdISP1 and rLdISP2 inferred strong interaction with C1complex and MASPs but rLdISP2 showed the stronger inhibitory effect on MASP2 than rLdISP1. Moreover, we found that rLdISP2 significantly reduces the formation of C3, C5 convertase and membrane attacking complex (MAC) by lectin pathway resulting in significant reduction in serum mediated lysis of the parasites. The role of LdISP2 on neutrophil elastase-mediated C5aR signaling was also evaluated. Notably, our results showed that infection of macrophages with ISP2OE Leishmania parasites significantly induces the expression of C5aR both at the transcript and translational level. Simultaneously, infection with ISP2KD parasites results in downregulation of host PI3K/AKT phosphorylation and increased in IL-12 production. Taken together, our findings clearly suggest that LdISP2 promotes parasite survival inside host by inhibiting MAC formation and complement-mediated lysis via lectin pathway and by up-regulation of C5aR signaling.